Factor VII Coagulant Activity in Relation to Serum Lipoproteins and Dietary Fat in Middle-aged Men - Väisänen, Sari; Rankinen, Tuomo; Penttilä, IIkka; Rauramaa, Rainer (Thrombosis and Haemostasis, 1995)
The associations of serum lipoproteins and habitual diet to factor VII coagulant activity (FVIIc) were analysed in 119 middle-aged men. FVIIc was measured by one-stage clotting assay, cholesterol and triglycerides enzymatically, serum apolipoproteins (apo) immunoturbi- dimetrically and habitual diet using four-day food records. ApoB, cholesterol, triglycerides, apoA-II, LDL cholesterol and dietary fat correlated directly to FVIIc (p <0.001). In multivariate analysis apoB, dietary fat and apoA-II explained 35.3% of the variance in FVIIc. In the lowest apoB tertile FVIIc was increased only when fat intake was high (>38 E%), in the middle tertile FVIIc increased gradually from low to high fat intake, whereas in the highest apoB tertile FVIIc was not related to dietary fat (p = 0.038 for age-adjusted interaction). The present data demonstrate a direct relation between apoB and FVIIc in middle-aged men. Low fat diet seem to associate to decreased FVIIc especially in subjects in the lower end of the apoB distribution.